1862 Miss. Laws 134 - (:unkn) unknown (My University, 1861)
Ch. 125: Prohibited any Sheriff or Tax-Collector to collect from any tax payer the tax previously assessed upon any Bowie-knife, sword-cane, or dirk-knife. None of the above items shall be given to tax assessors as taxable property.
Keywords: TAX - NON-GUN ARMS